2017
DOI: 10.1002/2017ja024419
|View full text |Cite
|
Sign up to set email alerts
|

Swept Forward Magnetic Field Variability in High‐Latitude Regions of Saturn's Magnetosphere

Abstract: Swept forward field is the term given to configurations of magnetic field wherein the field lines deviate from the meridional planes of a planet in the direction of its rotation. Evidence is presented for swept‐forward field configurations on Cassini orbits around Saturn from the first half of 2008. These orbits were selected on the basis of high inclination, spatial proximity, and temporal proximity, allowing for the observation of swept‐forward field and resolution of dynamic effects using data from the Cass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Kivelson et al (2002) state that the distance from the equator is a variable that can affect the direction of the azimuthal magnetic field, as higher latitudes may be influenced by an additional current system that closes the magnetospheric current. Following, Davies et al (2017) showed that swept-forward fields in the high latitudes are swept forward due to solar wind compressions and show modulation from planetary period oscillations, and hence, we may assume that swept-forward field seen at the equator may also be solar wind driven. As the aperiodic waves used to calculate the current density in the sheet are a direct sampling of the current sheet by Cassini, we can assume that this latitudinal effect is not affecting the data.…”
Section: Discussionmentioning
confidence: 99%
“…Kivelson et al (2002) state that the distance from the equator is a variable that can affect the direction of the azimuthal magnetic field, as higher latitudes may be influenced by an additional current system that closes the magnetospheric current. Following, Davies et al (2017) showed that swept-forward fields in the high latitudes are swept forward due to solar wind compressions and show modulation from planetary period oscillations, and hence, we may assume that swept-forward field seen at the equator may also be solar wind driven. As the aperiodic waves used to calculate the current density in the sheet are a direct sampling of the current sheet by Cassini, we can assume that this latitudinal effect is not affecting the data.…”
Section: Discussionmentioning
confidence: 99%